Whistleblowing Studies for Corruption Prevention in Indonesian Local Governments: A Systematic Literature Review - Waromi, Juliana; Falah , Syaikhul (Institut Bisnis dan Informatika Kesatuan, 2025)
Corruption remains a persistent challenge in Indonesian local governments, exacerbated by decentralization that increases fiscal autonomy and opportunities for misconduct. Weak internal controls, political interference, and cultural barriers often hinder early detection and prevention efforts. Whistleblowing systems offer a promising internal mechanism to address these issues by enabling insiders to report irregularities safely. This study aims to map the development of whistleblowing research focused on corruption prevention and detection in local government settings. A systematic literature review was conducted, analyzing fifty-eight international journal articles published between 2015 and 2025. The process followed a structured protocol with database searches, duplicate removal, and full-text eligibility assessment to ensure relevance and quality. Findings reveal a sharp rise in publications since 2020, reflecting growing policy attention. Key themes include reporting intentions, institutional protections, leadership influence, and digital integration. Whistleblowing serves dual roles in deterring potential fraud through perceived risks and uncovering actual malfeasance via insider tips. Effective implementation requires secure channels, strong legal safeguards, and supportive organizational cultures. The review concludes that whistleblowing strengthens governance integrity when embedded in comprehensive anti-corruption strategies. Local governments should prioritize anonymous digital platforms and leadership commitment to enhance reporting rates.